Little-known wingless crickets of Bhutan (Rhaphidophoridae): discovery and description of nine new species - Dorji, Cheten; Morgan-Richards, Mary; Trewick, Steven A. (Zootaxa, 2025)
We present the results of a survey of rhaphidophorids in Bhutan more than half a century since the first systematic exploration of orthoptera by the Natural History Museum Basel Expedition to Bhutan in 1972. Only one of two species previously described from Bhutan was resampled. A total of nine new species are described belonging to the family Rhaphidophoridae: five species in genus Diestramima Storozhenko (subfamily Aemodogryllinae), and four species in genus Rhaphidophora Serville (subfamily Rhaphidophorinae). We provide details of morphological structures for all newly described species and their known distribution and habitat. The phylogenetic relationships of the rhaphidophorids from Bhutan are inferred from mitochondrial DNA sequences (COI). New species of Diestramima are not assigned to subgenera because the shape of their paraproct is intermediate when compared to the shapes described for each subgenera. Keys to the Bhutan species based on male epiproct (Rhaphidophora) and posteromedian projection of 7th abdominal tergite (Diestramima) are provided. New species are Diestramima matermagna sp. nov., D. minjiwoonga sp. nov., D. multidenticuli sp. nov., D. samkhara sp. nov., and D. phubdorjia sp. nov.; Rhaphidophora bhutanensis sp. nov., R. bicuspis sp. nov., R. bilobata sp. nov., and R. piscicauda sp. nov..